Food waste in Czech households - Hrubá, Anna (2023)
The bachelor thesis addresses food waste in Czech households. Its main objective was to determine the proportion of food waste and the channels through which it exits, while also examining the impact of waste infrastructure on consumer behavior. Based on the collected data, the thesis proposes measures for a municipality to support optimal disposal and prevent the generation of food waste.